Prostatic relaxation induced by loperamide is mediated through activation of opioid μ-2 receptors in vitro - LU, CHIH-CHENG (D.A. Spandidos, 2011)
The merit of opioid μ-receptor activation in the improvement of benign prostatic hyperplasia (BPH) remains obscure. In the present study, we used loperamide to identify the subtype of opioid μ-receptors involved in prostatic relaxation and investigate the possible mechanism of this relaxation. Prostate strips were isolated from 12-week-old male Wistar rats for identification of isometric tension. The prostate strips were precontracted with either 1 μmol/l phenylephrine or 50 mmol/l KCl. The decrease in muscle tone (relaxation) was then characterized after cumulative administration of loperamide (0.1 to 10 μmol/l) into the organ bath for the concentration-dependent study. Pretreatment with specific blockers or antagonists was carried out to compare the changes in loperamide-induced relaxation. Loperamide produced a marked relaxation in the isolated prostates precontracted with phenylephrine or KCl in a dose-dependent manner. This relaxation was abolished by cyprodime, a selective opioid μ-receptor antagonist, but was not modified by naloxonazine at a dose sufficient to block the opioid μ-1 receptors. Treatment with an agonist for opioid μ-1 receptors also failed to modify the muscle tone. Moreover, the relaxation by loperamide was attenuated by glibenclamide at a dose sufficient to block ATP-sensitive K(+) channels. In addition, this action of loperamide was abolished by protein kinase A (PKA) inhibitor and enhanced by the inhibitor of phosphodiesterase for cyclic AMP (cAMP). Our results suggest that loperamide induces prostatic relaxation through activation of opioid μ-2 receptors via the cAMP-PKA pathway to open ATP-sensitive K(+) channels.